Intersectionality in U.S. Political Discourse: A Critical Analysis of Harris and Trump’s Rhetoric during the 2024 Presidential Election - El-Hamry, Soufiane (2025)
As the first woman of African American and South Asian origins to become a Vice President and a major party’s presidential candidate in America’s history, Kamala Harris represents an important case for exploring how political discourse negotiates ideological and power structures, and how intersectional identity constructs can be leveraged through rhetoric. Donald Trump’s political profile and rhetoric represent a counterpoint to examine how hegemonic identity-based politics are mobilized across the American political spectrum. By comparing Harris’ and Trump’s discoursal performances during the 2024 presidential election, this study seeks to analyze how gender, race, and class among other social categories intersect to shape political discourse in the US. It is an attempt to investigate how Harris navigated the power structures that mark American politics and employed her intersectional identity as a woman of color in her rhetoric and how Trump used his narrative as a White man. Using Critical Discourse Analysis as the primary methodological framework, this study analyzes the Harris-Trump debate in addition to eight speeches from each candidate based on intersectionality theory to interrogate how overlapping identities affect the negotiation of power and production of political discourse in contemporary America.